Sheltering eaves. 1 - Aruga, Rie (Kodansha, 2024)
"High schooler Yoru was sent to a group home at the age of ten after her mother abused her. Tenjaku, a boy the same age, took her under his wing. Now, as teenagers, Yoru and Tenjaku only have a year left before they are legally required to leave the home, and they mustpack a lot of growing up into a short period of time. The foremost decision in Yoru's mind: what to do about the feelings for Tenjaku that she's sheltered in her heart during their years together..."--Provided by publisher.